Analisis Berbagai Faktor Yang Melatarbelakangi Seseorang Penyalahgunaan Narkoba - muarrofah muarrofah (LPPM Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2019)
The research desain is sectional cross analytic by 200 population of convicted criminal in using drugs abuse in 20-29 years in society institute of drugs at Pamekasan II a class and sample total is 133 convicted criminal by simple technic of random while collecting data by using kuesioner. the result of this research is found of any factor namely factor of family is 99 responders (74,4%), factor of strong minded is 68 responders (51,5%), factor of mentals stress is 73 (54,9%), Factor of drugs addict by dependecing drug more is 76 responders (57,1%), but as is chi square test by SPSS is found in Factor of family by (p = 0,008%), factor of strong minded by (p=0,002), invited by friend factor by (p=0,001), factor of mental stress by (p=0.014), so that these research can be conclutioned that factor of familly, factor of drug addict by dependencing drug, invited by friend factor , factor of mental stress by using abuse.